Land Management Rights Before and After the Government Regulation in Lieu of Job Creation Law - Penta Peturun (Administrative and Environmental Law Review, 2023)
There are regulations regarding land management rights (HPL) in Law Number 11 of 2020 concerning Job Creation in Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation. The background is the birth of the Investment policy made by President Joko Widodo's Government. HPL is regulated separately as a “right”, whereas in the Basic Regulations on Agrarian Principles (UUPA) which is the source of law, there is no mention of “rights”. Related to the authority of the State's Right to Control (HMN). The Government Regulation transfers HPL as a whole to certain parties. There should be a role for regulators and operators participating in planning, implementation and supervision. Therefore, there must be clarity on the position of the authority “controlled by the state” for HMN constitutionally against HPL in Government Regulations that refer to the constitution. In a normative legal approach, Article 33 of the 1945 Constitution mandates the state to conduct beleid, bestuursdaad, regelendaad, beheersdaad, tezichthoudensdaad. Philosophically, the government functions as a regulator and operator. As an operator, the Government carries out its duties as a coach and supervisor by directly implementing activities. This is confirmed in the Decision of the Constitutional Court of the Republic of Indonesia Number 001-21-22-PUUI 2003 on HMN. Suppose HPL in the Government Regulation is released. In that case, it is not much different from embracing the concept of nachtwachternstaat or night watchman state, not the principle of welvaarstaat which fully utilizes the control of wealth sources for the greatest prosperity of the people. As it should be, HPL in HMN can provide direction for law enforcers and stakeholders with a role and authority in the land acquisition process.